Self‐Repairing Tin‐Based Perovskite Solar Cells with a Breakthrough Efficiency Over 11%. Issue 31 (25th June 2020) - Wang, Chengbo; Gu, Feidan; Zhao, Ziran; Rao, Haixia; Qiu, Yaming; Cai, Zelun; Zhan, Ge; Li, Xiaoyue; Sun, Boxun; Yu, Xiao; Zhao, Boqin; Liu, Zhiwei; et al.
Abstract: The development of tin (Sn)‐based perovskite solar cells (PSCs) is hindered by their lower power conversion efficiency and poorer stability compared to the lead‐based ones, which arise from the easy oxidation of Sn 2+ to Sn 4+ . Herein, phenylhydrazine hydrochloride (PHCl) is introduced into FASnI3 (FA = NH2 CH  NH2 + ) perovskite films to reduce the existing Sn 4+ and prevent the further degradation of FASnI3, since PHCl has a reductive hydrazino group and a hydrophobic phenyl group. Consequently, the device achieves a record power conversion efficiency of 11.4% for lead‐free PSCs. Besides, the unencapsulated device displays almost no efficiency reduction in a glove box over 110 days and shows efficiency recovery after being exposed to air, due to a proposed self‐repairing trap state passivation process. Abstract : Phenylhydrazine hydrochloride is introduced into FASnI3 ‐based perovskite solar cells (where FA = NH2 CHNH2 + ) in order to reduce the existing Sn 4+ and prevent the further degradation of the FASnI3 . Consequently, the champion device shows a high power conversion efficiency up to 11.4%, a long‐term storage stability over 2300 h, and an efficiency recovery capability after being exposed to air.